Inside pitch: Life in professional baseball - Gmelch, George (London University of Nebraska Press, 2006)
From the spark of ambition to play baseball professionally to the necessity of reinventing life after baseball, the anthropologist and former Minor Leaguer George Gmelch describes the lives of the men who work at America's national game. Twenty-four years after his own final road trip as a minor leaguer, Gmelch went back on the road with ballplayers, this time with a pen and pad to record the details of life around the diamond.